Arrest of the Mw 6.8 January 24, 2020 Elazig (Turkey) earthquake by shallow fault creep - Cakir, Ziyadin; Dogan, Ugur; Akoglu, Ahmet M.; Ergintav, Semih; Ozarpaci, Seda; Ozdemir, Alpay; Bilham, Roger (Elsevier, 2023)
It has long been conjectured that creeping sections of strike slip faults arrest or subdue earthquake rupture, partly because of their reduced slip potential and partly because of their velocity-strengthening frictional properties. However, no instrumentally recorded large earthquake (Mw >= 6.8) on any well instrumented continental strike-slip fault has thus far occurred that has clearly been arrested at a region of fault creep, rendering it difficult to identify experimentally the parameters that control rupture arrest. Nearfield GPS, InSAR and creepmeter data from the 2020 Elazig (Turkey) earthquake reveal not only how rupture propagation of a large earthquake is hindered by shallow creep reducing the earthquake size, but also provide important quantitative insights into the late interseismic, coseismic and post seismic behavior of a creeping fault, which has important implications for evaluating hazard potential of a major earthquake on a creeping fault, such as has been forecast for the Hayward fault in California. (c) 2023 Elsevier B.V. All rights reserved.
Keywords: rupture arrest; creep; afterslip; earthquake cycle